Shared decision making: audiology student perspectives - Hussain, S.; Wilkes, C.; Dhanda, N. (Frontiers in Rehabilitation Sciences, 2023)
Introduction Shared decision making is a concept in healthcare that actively involves patients in the management of their condition. The process of shared decision making is taught in clinical training programmes, including Audiology, where there are several options for the management of hearing loss. This study sought to explore the perception of Healthcare Science (Audiology) student views on shared decision making. Methods Twelve students across all years of the BSc Healthcare Science degree took part in three semi-structured focus groups. Four students were work-based learners, and eight students were enrolled on the standard pathway. Data were analysed using Thematic Analysis. Results Students’ definition and understanding of shared decision making was influenced by three key factors that were based on using a range of resources, implementation of a decision aid, and recognising Ida Institute as a pinnacle of shared decision making. Students also identified their roles as the future of healthcare workforce and the importance of disseminating best practice. Conclusion Shared decision making is valued by students in their roles as healthcare trainees. This study data will enhance teaching practices for healthcare science students in audiology training. Future research involving patient views in clinical training is vital.